Robot system reliability and safety: a modern approach - Dhillon, B.S. (Boca Raton, FL, 2015)
"As robots are used more and more to perform a variety of tasks in a range of fields, it is imperative to make the robots as reliable and safe as possible. Yet no book currently covers robot reliability and safety within one framework. Robot System Reliability and Safety: A Modern Approach presents up-to-date information on robot reliability, safety, and related areas in a single volume, eliminating the need to consult diverse sources. After introducing historical, mathematical, and introductory aspects, the book presents methods for analyzing robot system reliability and safety. It next focuses on topics related to robot reliability, including classifications of robot failures and their causes and hydraulic and electric robots’ reliability analysis. The book then explains the analysis of robot-related safety and accidents, covers key elements of robot maintenance and robotics applications in maintenance and repair, and addresses human factors and safety considerations in robotics workplaces. The book concludes with chapters on robot testing, costing, and failure data as well as six mathematical models for reliability and safety analysis. Written by a well-known expert in reliability engineering, this book will be useful to system, design, reliability, and safety engineers along with other engineering professionals working in the area of robotics. It can also be used in courses on system engineering, reliability engineering, and safety engineering."